2017
DOI: 10.2174/1874325001711011466
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Theories of Adolescent Idiopathic Scoliosis: Past and Present

Abstract: Adolescent idiopathic scoliosis is one of the most common spinal deformities, yet its cause is unknown. Various theories look to biomechanical, neuromuscular, genetic, and environmental origins, yet our understanding of scoliosis etiology is still limited. Determining the cause of a disease is crucial to developing the most effective treatment. Associations made with scoliosis do not necessarily point to causality, and it is difficult to determine whether said associations are primary (playing a role in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 232 publications
(184 reference statements)
1
90
0
13
Order By: Relevance
“…Asynchronous neuro-osseous growth of the spinal column and cord has also been suggested to play a role in AIS [9]. The observation that the thoracic spine is longer anteriorly than posteriorly in AIS patients, a phenomenon known as relative anterior spinal overgrowth (RASO) or an uncoupled neuroosseous growth, has now been corroborated with many anatomical and MRI studies [25][26][27][28][29][30]. Brink et al evaluated the cause of anterior-posterior length discrepancy and showed that it was a consequence of both anterior and posterior column shortening and whilst the vertebrae contribute to the length discrepancy, it is mostly due to the secondary increased anterior intervertebral discs height [29].…”
Section: Abnormal Skeletal Growth and Biomechanical Theoriesmentioning
confidence: 89%
See 1 more Smart Citation
“…Asynchronous neuro-osseous growth of the spinal column and cord has also been suggested to play a role in AIS [9]. The observation that the thoracic spine is longer anteriorly than posteriorly in AIS patients, a phenomenon known as relative anterior spinal overgrowth (RASO) or an uncoupled neuroosseous growth, has now been corroborated with many anatomical and MRI studies [25][26][27][28][29][30]. Brink et al evaluated the cause of anterior-posterior length discrepancy and showed that it was a consequence of both anterior and posterior column shortening and whilst the vertebrae contribute to the length discrepancy, it is mostly due to the secondary increased anterior intervertebral discs height [29].…”
Section: Abnormal Skeletal Growth and Biomechanical Theoriesmentioning
confidence: 89%
“…Stokes et al later proposed their vicious cycle hypothesis whereby asymmetric loading in a "vicious cycle" causes vertebral wedging during growth in progressive scoliosis curves. Their hypothesis implies that regardless of the initial cause of scoliosis, mechanical factors increase significantly during periods of rapid adolescent growth, when risk of curve progression is greatest [28,34].…”
Section: Abnormal Skeletal Growth and Biomechanical Theoriesmentioning
confidence: 99%
“…However, a review article reported that there is no perfect study of the etiopathogenesis of AIS with advanced understanding of the mechanisms of melatonin in the development of AIS in humans [42]. In addition, the prevalence of scoliosis was higher in adolescents who participated in various sport activities [14]. However, most studies were retrospective caseecontrol studies; hence, further studies are needed to suggest that flexibility or hypermobility in some sports leads to AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Puberty is thought to be initiated by genetic and lifestyle factors, leading to the development of AIS [13]. In addition, melatonin deficiency and joint hypermobility during exercise have been shown to be related to increased prevalence of scoliosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is the most common form and in 80% of cases occurs in girls. The etiopathogensis of this disorder appears to be multifactorial with a genetic tendency to the deformity, which is triggered by biomechanical, neuromuscular, genetic, hormonal and environmental factors [1,2].…”
Section: Introductionmentioning
confidence: 99%